Development of a unified design buckling curve for fibre reinforced polymer plates subjected to in-plane uniaxial and uniform compression - Olsson, Erik; Mottram, J. Toby; Al-Emrani, Mohammad; Haghani, Reza (Thin-walled structures, 2023)
Presented are 24 non-dimensional buckling curves to estimate the strengths of Fibre-Reinforced Polymer (FRP) square plates having four simply supported edges and subjected to in-plane uniaxial and uniform in-plane compression. The curves are constructed by the authors from a parametric numerical analysis using ABAQUS® software with changing variables for: material properties; initial geometrical imperfections; laminate lay-ups; and plate thicknesses. These strength curves express relationships for the buckling reduction factor with plate slenderness, and account for post-buckling strength. We observe that regardless of the laminate lay-up (except for purely unidirectional), the choice of FRP material and the magnitude of the initial geometrical imperfection the predicted buckling reduction factors display a meaningful correlation with plate slenderness. Presented is a proposed unified buckling design curve, defined as the lower bound to 18 of the 24 ABAQUS®-generated buckling curves. This new curve is benchmarked by the authors against experimental test results extracted from the literature and it is found that there is a reasonable agreement. The authors recommend that the proposed buckling design curve has the potential to be introduced into structural design standards as a procedure to design the buckling strengths of FRP plates.